Successful extracorporeal membrane oxygenation implantation in a patient with isolated postcardiotomy right ventricle failure: a case report - Kolcow, Walenty; Keita, Luther; Steter, Daniel; Ahmet, Suhaib; Abse, Tony; Costa, Mark Da (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
We present a case of a 63-year-old male who developed isolated right ventricle (RV) failure after routine aortic valve replacement (AVR). One hour after the operation, extracorporeal membrane oxygenation (ECMO) circuit was implanted as a temporary right ventricle assist device (RVAD). A few hours after that when ECMO support was established, inotropic support was significantly reduced and metabolic acidosis was corrected. After 42 hours of support, ECMO was successfully removed. The patient was discharged home after 34 days of hospital stay. Pre-discharge transthoracic echocardiography (TTE) revealed good RV and left ventricle (LV) function and normally functioning tissue AVR. Eight months later the patient underwent a successful hip and knee replacement. Three years after his cardiac surgery, the patient remains in New York Heart Association heart failure classification (NYHA) class I.